The challenges of the leverage ratio - Samuels, Simon (Henry Stewart Talks, 2016)
Regulatory framework effects on US / EU banking systems, Problems with the Basel ratio, The leverage ratio at a divisional level, The leverage ratio and profitability, From Basel III to Basel IV